Ginges : construção de um personagem - Massaro, Felipe Karpinski (2022)
This doctoral thesis is presented within the context of a Creative Writing program and is divided into two parts: a literary and a reflective work. In the first part, I present an unpublished novella, Ginges, which tells the story of an anarcho-seer with some problems to solve. After presenting the novella, I reflect on the writing process as an addendum to the literary work, focusing on character construction.